(untitled) - Nguyễn Duy Cần (Bangkok, 1994)
For the purpose of understanding the existing farming systems and to help farmers to improve their farming practices, a survey was conducted to diagnose the major farming systems. The study area consists of two categories, shallow and semideep rainfed. In this study, four major farming systems, rice monoculture, rice-shrimp, rice-upland crop and rice-fish system are described.
Keywords: farming management